Scenarios of militarization of everyday life in american horror films. Part 2 / Сценарии милитаризации повседневности в американских фильмах ужасов. Часть 2 - Sergey Malenko / Сергей Анатольевич Маленко; Andrey Nekita / Андрей Григорьевич Некита (Индустрии впечатлений: Технологии социокультурных исследований)
In the second part of the article, the authors continue to analyze the militaristic practices of Hollywood, which have been comprehensively tested on the extensive visual material of American horror films. Militarization of everyday life quite naturally becomes one of the leading themes of this genre. Moreover, the everyday life of the elite representatives paradoxically turns out to be much more intimidating than the life of ordinary Americans. Two very successful Hollywood film projects – “American Psychopath” by Mary Harron and “The Game” by David Fincher become direct artistic material for analysis. Successful banker Patrick Bateman turns into a notorious sadist within the boundaries of his home, taking revenge on his elite colleagues for the forced comfort of official elite existence. The theme of elite horror is continued by the character of Michael Douglas, who embodied the phantasmagoric suffering of a man who paid for his professional success with the collapse of his business reputation and a prosperous personal lifein the image of Nicholas Van Orton. Thus, the American horror film consistently and professionally promotes biopolitical conflicts and low-intensity wars as the essence of elite social communication and the ideal of personal self-improvement. Во второй части статьи авторы продолжают анализ милитаристских практик Голливуда, которые были всесторонне апробированы на обширном визуальном материале американских фильмов ужасов. Милитаризация повседневности совершенно закономерно становится одной из ведущих тем этого жанра. Причем, повседневность представителей элиты парадоксальным образом оказывается гораздо более устрашающей, нежели жизнь обычных американцев. Непосредственным художественным материалом для анализа становятся два очень успешных голливудских кинопроекта – «Американский психопат» Мэри Хэррон и «Игра» Дэвида Финчера. Успешный банкир Патрик Бэйтман в границах своего дома превращается в отъявленного садиста, мстящего своим элитным коллегам за вынужденную комфортность официального элитного бытия. Тему элитного ужаса продолжает персонаж Майкла Дугласа, воплотившего в образе Николаса Ван Ортона фантасмагорические страдания человека, заплатившего за свой профессиональный успех крушением деловой репутации и благополучной личной жизнью. Таким образом, американский фильм ужасов последовательно и профессионально пропагандирует биополитические конфликты и войны малой интенсивности как сущность элитной социальной коммуникации и идеала личностного самосовершенствования.